Multiple Actin Isotypes in Plants: Diverse Genes for Diverse Roles? - Šlajcherová, Kateřina; Fišerová, Jindřiška; Fischer, Lukáš; Schwarzerová, Kateřina (Frontiers in Plant Science, 2012)
Plant actins are encoded by a gene family. Despite the crucial significance of the actin cytoskeleton for plant structure and function, the importance of individual actin isotypes and their specific roles in various plant tissues or even single cells is rather poorly understood. This review summarizes our current knowledge about the plant actin gene family including its evolution, gene and protein structure, and the expression profiles and regulation. Based on this background information, we review mutant and complementation analyses in Arabidopsis to draw an emerging picture of overlapping and specific roles of plant actin isotypes. Finally, we examine hypotheses explaining the mechanisms of isotype-specific functions.